Self-esteem and stress among adult stutters visiting in stutter's association of Nepal. - Tamang, Rashmi
ABSTRACT: Stuttering also called as stammering which is characterized by involuntary repetition of words. It leads to disturbance in communication. Different treatment modalities are available for stuttering among them speech therapy is one of the most effective option. The objective of the study was to assess self-esteem and stress among stutterers. Descriptive survey design was used. Approximately 86 stutterers were selected by using nonprobability purposive sampling method and data was collected through semi-structured interview schedule. The collected data were entered in SPSS version 20 and analyzed using descriptive statistical methods like frequency, percentage, mean and standard deviation. Inferential statistics namely Chi-square test was used to show association between selected variables and Karl Pearson's correlation coefficient was used to analyze the correlation between self-esteem and stress among stutterers. In this study, highest proportion (43%) of respondents were aged 19-28 years and most (89.5%) of the respondents were male. Similarly, majority (54.7%) of respondents were enrolled in speech therapy. Almost all (91.9%) of respondents agreed that support group have been helpful. Finding revealed that 46.5% had high level of self-esteem and 52.3% had mild level of stress among stutterers. Finding revealed significant association between level of stress and stuttering support group. The finding of the study concludes that there is strong positive correlation between level of self-esteem and stress among stutterers. The support group helps to reduce the stress and increase the self-esteem of stutterers so, the concerned authority should recommend enhancing and increasing the activation of support group. Key words: Stuttering, Self-esteem, Stress, Speech therapy, Support group